2022
DOI: 10.1002/ajoc.202200473
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Efficient Cu@SiO2 Catalyst: Enabled Nucleophilic and Electrophilic Activation of Active Methylene Compounds

Abstract: The utility of copper is strikingly afforded due to the variable oxidation state being widely used in various organic reactions. The copper-catalyzed CÀ C bond formation with active methylene compounds are a straightforward approach with widespread uses in synthetic organic chemistry. A significantly lower amount of Cu-supported SiO 2 catalyst was synthesized through sol-gel method. The microscopy analysis reveals the formation of spherical morphology and the uniform distribution of Cu nanoparticles of 2.5 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The catalyst's structure depends on factors such as copper loading, method of synthesis, and calcination conditions. Cu/SiO 2 catalysts exhibit excellent catalytic activity for various reactions, including hydrogenation, dehydrogenation, oxidation, and coupling reactions [10,[57][58][59][60]. The presence of Cu nanoparticles on the SiO 2 support enhances the catalyst's performance due to its high surface area and dispersion of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst's structure depends on factors such as copper loading, method of synthesis, and calcination conditions. Cu/SiO 2 catalysts exhibit excellent catalytic activity for various reactions, including hydrogenation, dehydrogenation, oxidation, and coupling reactions [10,[57][58][59][60]. The presence of Cu nanoparticles on the SiO 2 support enhances the catalyst's performance due to its high surface area and dispersion of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…[11] One such approach is the condensation between a carbonyl compound and an active methylene moiety-possessing molecule with the utilization of a wide variety of catalysts including mesoporous materials, metal-organic frameworks, bimetallic, mixed oxide, graphitic carbon nitride, and deep eutectic solvents. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Further, hazardous solvents including tetrahydrofuran, [32,33] dimethyl formamide, [34] alcohols, [35,36] dioxane, [37] toluene, [38] acetonitrile, [39] and dichloromethane [40] have often been used to effect this carbon-carbon bond construction. [41][42][43][44][45][46][47] For instance, Hassan et al [41] showed the capacity of amino-grafted graphene oxide-Fe 3 O 4 in tetrahydrofuran at 50 C, Markad et al [44] exposed the performance of amidefunctionalized 2D coordination polymer (involving a bis-pyridylmethyldiaminobutane diacetamide) in methanol, Taher et al [45] revealed the amine-functionalized metal-organic framework in DMF, Zhong et al [46] discovered the utility of bifunctional mesoporous carbon nitride in toluene at 80 C under ...…”
Section: Introductionmentioning
confidence: 99%